Optimal Redistributive Pensions and the Cost of Self-Control - Pier-André Bouchard St-Amant; Jean-Denis Garon (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine how the introduction of self-control preferences influences the trade-off between two fundamental components of a public pension system: the contribution rate and its degree of redistribution. The pension regime affects individuals' welfare by altering how yielding to temptation (i.e. not saving, or saving less) is attractive. We show that proportional taxation increases the cost of self-control, and that this adverse effect is more acute when public pensions become more redistributive.
Keywords: H55; H21; D03; 330; taxation; redistribution; pensions; self-control